Analisis Pendapatan dan Biaya Operasional terhadap Laba Usaha pada Antero Hotel Jababeka - Asrul; Sri Waluya (Mulia Pratama, 2022)
This study aims to determine how much the variables of Income and Operational Costs have a significant effect on Operating Profit at Antero Hotel Jababeka and to find out whether the Operational Cost control that is carried out can increase or decrease operating profit at Antero Hotel Jababeka. The data were analyzed using quantitative methods using financial statement data, especially the Balance Sheet and Profit and Loss Statement by using a case study approach. The results of the research include, in 2018 the income earned was Rp. 13,643,852,440 with operational costs of Rp. 12,271,948,067 and generate a profit of Rp. 312,832,709. While in 2019 the income earned was Rp. 12,587,126,951 and the operational costs incurred are Rp. 9,926,191,346 and generate a profit of Rp. 1,005,848,084. In 2019 the operating profit obtained was higher than in 2018, this is because the efficiency of operating cost control carried out by the hotel has a very positive effect so that it can increase operating profit in 2019. And in 2020 the income earned was Rp. 2,485,783,144 with operational costs that are Rp. 1,955,816,548 by generating an operating profit of Rp. 475,580,750 in which the operating profit earned was very low compared to 2018 and 2019. This is because during the covid-19 pandemic the hotel only operated until the middle of the year or about 6 months because the income generated was no longer stable and the operational costs incurred are also not small, therefore the hotel decided to take a strategy to temporarily stop operating until the pandemic subsides.